Promoting parental acceptance of bisexuality: A case study of attachment-based family therapy. Issue 3 (3rd July 2018) - Ibrahim, Maliha; Russon, Jody; Levy, Suzanne; Diamond, Guy
ABSTRACT: Attachment-based family therapy is an empirically supported, manualized treatment spanning over 15 years of research and clinical practice. Increasingly, research and clinical evidence emphasize the modification of family therapy models to meet the needs of diverse clients. Best practices require culturally-sensitive therapists to attend to issues of race, gender identity, sexual orientation, ethnicity, class, and ability. The ABFT model has been evolving to address the health disparities associated with marginalization and attend to the specialized needs of diverse families. This clinical case study demonstrates how ABFT clinicians must adopt an intersectional approach to be successful in building and sustaining relational repair. Transcripts from a case with a religious, African-American family and their bisexual daughter outline the structure and sequence of ABFT. An analysis of this case illustrates the impact of intersectionality on clinical processes and mechanisms of change.